From Photons to Higgs : A Story of Light - Han, Moo-Young (Singapore ; World Scientific Pub. Co., 2014)
This book presents a brief introduction to the quantum field theory of the Standard Model for quarks and leptons. With minimal use of mathematics, it covers the basics of quantum field theory, local gauge field theory, spontaneous symmetry breaking mechanism, the Higgs mechanism and quantum chromodynamics. From the time when the first edition was published until today, the field of particle physics has seen some major break-through with the possible discovery of Higgs particle, also known as the Higgs boson. In the second edition, the famous Higgs mechanism is included to explain the symmetry breaking in the Standard Model and the origin of mass, and all of this is explained in high-school level algebra. Aimed at both scientists and non-specialists, it requires only some rudimentary knowledge of the Lagrangian and Hamiltonian formulation of Newtonian mechanics as well as a basic understanding of the special theory of relativity and quantum mechanics to enjoy this book.
1. Particles and fields I: Dichotomy -- 2. Lagrangian and Hamiltonian dynamics -- 3. Canonical quantization -- 4. Particles and fields II: Duality -- 5. Equations for duality -- 6. Electromagnetic field -- 7. Emulation of light I: Matter fields -- 8. Road map for field quantization -- 9. Particles and fields III: Particles as quanta of fields -- 10. Emulation of light II: Interactions -- 11. Triumph and wane -- 12. Leptons and quarks -- 13. What is gauge field theory? -- 14. The weak gauge fields -- 15. The Higgs mechanism and the electroweak gauge fields -- 16. The Higgs particle -- 17. Evolution of the strong force -- 18. The history of color SU(3) symmetry -- 19. Quantum chromodynamics, QCD.
Includes index.
Electronic reproduction.
Keywords: Photons; Higgs bosons; Electronic books